Method of Dose Delivery in Brachytherapy for Cervical Cancer - D. I. Kazlouski; A. A. Suslava; I. Y. Dubik; Y. I. Kazlouskaya; V. A. Suslava; N. A. Artemova; I. H. Tarutin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
A method is proposed for delivering an absorbed dose to a target during brachytherapy for cervical cancer by using a new applicator, which consists of an annular part and two uterine canals. The design of the applicator makes it possible to implement it to the required depth, taking into account the anatomical features, to widely cover the cervix and corporis of a womb with a 100 % isodose of irradiation, which makes it possible to deliver the planned dose. The patient admitted to the brachytherapy department received the first treatment fraction using the Interstitial Ring applicator, the second and subsequent fractions were performed using the proposed applicator (6 fractions in total). In comparison with the standard applicator Interstitial Ring, the use of the proposed applicator made it possible to increase the coverage of the target with the prescribed dose from 69.2 to 95.5 %. This led to an increase in the absorbed dose per target for a course of radiation therapy from the planned 70.4 to 85.4 Gy. Twelve treatment plans for 3 patients were analyzed using different dose fractionation schemes. In all three cases, it was possible to increase the coverage of the target with the prescribed dose, which led to an increase in the total absorbed dose per target, which was more than 85 Gy. The proposed method has been successfully applied in the N. N. Alexandrov National Cancer Centre during brachytherapy for cancer of the cervix and corporis of a womb.